Solitary Polypoid Angiodysplastic Lesion Mimicking a Tumor in the Jejunum. Issue 1 (2017) - Polavarapu, Abhishek D.; Kesavan, Mayurathan; Gumaste, Vivek V.; Wrzolek, Monika; Purow, Elias
ABSTRACT : N/A: Small bowel bleeding should be considered in patients with overt or occult gastrointestinal hemorrhage after normal upper and lower endoscopic examination. Angiodysplasia appearing as multiple flat vascular tufts is the most common cause of small bowel bleeding in patients over 40 years old. Polypoid angiodysplasia, however, is extremely rare. This report illustrates a unique case of solitary polypoid angiodysplasia in the jejunum of an adult with chronic kidney disease, who presented with an occult gastrointestinal bleed. The angiodysplasia mimicked tumorous growth, potentially indicative of malignant neoplasm. The patient underwent surgical resection and was histologically diagnosed as having angiodysplasia.